Cell Mechanisms of Post-Mortem Excitability of Skeletal Muscle - H. Stigter; T. Krap; W. L. J. M. Duijst (Biomedicines)
Background/Objectives: The excitability of skeletal muscle is a less-known post-mortem supravital phenomenon in human bodies, and it can be used to estimate the post-mortem interval. We conducted a field study in the Netherlands to investigate the applicability of muscle excitability (SMR) by mechanical stimulation for estimating the post-mortem interval in daily forensic practice. Knowledge concerning the post-mortem cell mechanisms accounting for the post-mortem excitability of skeletal muscle is lacking. Cell mechanisms are the specific intracellular and biochemical processes responsible for post-mortem muscle excitability. Methods: We have studied the theoretical backgrounds of the cell mechanisms that might be responsible for post-mortem muscle excitability, by performing literature research via the databank PubMed. Results: Based on the current available literature, in our opinion the intracellular changes in muscle cells that are responsible for SMR resemble the intracellular processes responsible for muscle fatigue due to energy exhaustion in the living. Conclusions: We hypothesize two pathways, depending on the level of energy in the muscle cell, that could be responsible for post-mortem muscle excitability by mechanical stimulation.